Innovative and Promising Strategies to Enhance Effectiveness of Immunotherapy for CNS Tumors: Where Are We? - Quintarelli, Concetta; Camera, Antonio; Ciccone, Roselia; Alessi, Iside; Del Bufalo, Francesca; Carai, Andrea; Del Baldo, Giada; Mastronuzzi, Angela; De Angelis, Biagio (Frontiers in Immunology, 2021)
Although several immune-therapies for the treatment of Central Nervous System (CNS) tumors are under evaluation, currently none of the approaches has received approval from the regulatory agencies. CNS tumors, especially glioblastoma, are tumors characterized by highly immunosuppressive tumor microenvironment, limiting the possibility of effectively eliciting an immune response. Moreover, the peculiar anatomic location of these tumors poses relevant challenges in terms of safety, since uncontrolled hyper inflammation could result into pictures of cerebral edema and cranial hypertension. The most promising strategies of immunotherapy in neuro-oncology consist of the use of autologous T cells redirected against tumor cells through chimeric antigen receptor (CAR) constructs or genetically modified T-cell receptors. Trials based on native or genetically engineered oncolytic viruses and on vaccination with tumor-associated antigen peptides are under evaluation, as well. Despite some sporadic complete remissions achieved in clinical trials, the outcome of patients with CNS tumors given different immunotherapeutic approaches aimed at increasing T cell reactivity towards the tumor remains poor. Based on the lessons learnt from these unsatisfactory experiences, combinatorial immune-therapy approaches aimed at overcoming the profound immunosuppressive microenvironment of these diseases are bringing new hope for the future of immunotherapy for CNS tumors.